Phospholipase D2 loss results in increased blood pressure via inhibition of the endothelial nitric oxide synthase pathway - Rochelle K. Nelson (Nature Portfolio, 2017)
Abstract The Phospholipase D (PLD) superfamily is linked to neurological disease, cancer, and fertility, and a recent report correlated a potential loss-of-function PLD2 polymorphism with hypotension. Surprisingly, PLD2 −/− mice exhibit elevated blood pressure accompanied by associated changes in cardiac performance and molecular markers, but do not have findings consistent with the metabolic syndrome. Instead, expression of endothelial nitric oxide synthase (eNOS), which generates the potent vasodilator nitric oxide (NO), is decreased. An eNOS inhibitor phenocopied PLD2 loss and had no further effect on PLD2 −/− mice, confirming the functional relationship. Using a human endothelial cell line, PLD2 loss of function was shown to lower intracellular free cholesterol, causing upregulation of HMG Co-A reductase, the rate-limiting enzyme in cholesterol synthesis. HMG Co-A reductase negatively regulates eNOS, and the PLD2-deficiency phenotype of decreased eNOS expression and activity could be rescued by cholesterol supplementation and HMG Co-A reductase inhibition. Together, these findings identify a novel pathway through which the lipid signaling enzyme PLD2 regulates blood pressure, creating implications for on-going therapeutic development of PLD small molecule inhibitors. Finally, we show that the human PLD2 polymorphism does not trigger eNOS loss, but rather creates another effect, suggesting altered functioning for the allele.